An Ontology-Based Approach for Software Measurement Systems Integration - Fonseca, Vinícius Soares; Barcellos, Monalessa Perini; Falbo, Ricardo de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2016)
Software measurement is performed in the context of various software processes that, generally, have different supporting tools. Thus, organizations have to deal with integration issues to enable the communication between tools and to properly support the measurement process. A key factor for integration is that tools share a common understanding regarding the meaning of the exchanged terms and services, i.e., it is important to deal with integration at the semantic level. Ontologies have been acknowledged as an important means to address semantic integration. In this paper we present the Ontology-Based Approach for Measurement Systems Integration (OBA-MSI), an approach that uses ontologies as a basis to integrate tools aiming at supporting the software measurement process. In order to evaluate OBA-MSI, it was applied to integrate tools in a software development organization.